RELATIONSHIP BETWEEN COMMUNITY KNOWLEDGE OF TUBERCULOSIS AND TUBERCULOSIS TRANSMISSION PREVENTION PRACTICES IN THE WORKING AREA OF GOLAGO KUSUMA PUBLIC HEALTH CENTER - Yohanes Tri Anggoro Yohanes Tri Anggoro; Dion Kunto Adi (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Abstract Background: Community participation in adopting preventive behaviors plays an important role in controlling tuberculosis (TB) transmission at the primary healthcare level. Aim: To analyze the relationship between community knowledge and tuberculosis transmission prevention practices in the Golago Kusuma Public Health Center service area. Method: This quantitative study employed a cross-sectional design involving 110 respondents selected using accidental sampling. Data were collected using structured questionnaires and analyzed using descriptive statistics and the Chi-square test with a significance level of α = 0.05. Results: Most respondents had a moderate level of knowledge (40.0%), while tuberculosis transmission prevention practices were also predominantly at a moderate level (46.4%). The Chi-square test showed a statistically significant relationship between community knowledge and tuberculosis transmission prevention practices (χ² = 99.282; p < 0.001). Respondents with higher levels of knowledge tended to demonstrate better prevention practices. Conclusion: Community-based health education needs to be strengthened to improve prevention practices and support more effective tuberculosis control at the primary healthcare level. Keywords: Tuberculosis, Community Knowledge, Prevention Practices